Strategies for the introduction and implementation of a guideline for the treatment of type 2 diabetics by general practitioners (GPs) of the Lazio region of Italy (IMPLEMEG study): Protocol for a cluster randomised controlled trial [ISRCTN80116232] - Perria Carla (BMC, 2004)
Abstract Background Despite broad agreement on the necessity to improve quality of diabetic care through implementation of clinical guidelines, in Italy many people with diabetes still lack adequate care in general practice. In addition there is little evidence to support the choice of implementation strategies, especially in the Lazio region (central Italy), where comparative studies among general practitioners (GPs) are uncommon. The primary objective of the study is to assess the effectiveness of different strategies for the implementation of an evidence-based guideline for the management of non-complicated type 2 diabetes mellitus (DM) among GPs of the Lazio region. Methods/Design Three-arm cluster-randomised trial (C-RCT). 252 GPs were randomised either to arm 1 (comprising a training module and administration of the guideline), or to arm 2 (administration of guideline without training), or to arm 3 (control arm), continuing current practice. Arm 1 participants attended a two-day course with CME credits. Data collection will be performed using current information systems. Patients' health data was also collected to describe diabetic populations cared for by GP participants. Process outcomes will be measured at the patient level and at the cluster level one year after the intervention. We will assess GPs' adherence to guideline recommendations for diabetes management relative to: 1) pharmacological management of diabetes; 2) pharmacological management of cardiovascular risk factors (hypertension and dislypidaemia); 3) measurement of glycosilated haemoglobin as the principal indicator of glycaemic control; 4) micro- and macrovascular complications assessment tests. Outcomes will be expressed as proportions of patients cared for by GPs who will have prescriptions of drugs, requests for tests and for outpatient appointment visits. To estimate the efficiency of resource use associated with the intervention a cost-effectiveness analysis will be carried out. The design of the study is based on three Cochrane and one Health Technology Assessment systematic reviews of guideline dissemination and implementation strategies.